Development of a Business Database and Clustering of Aisyiyah Family Enterprises to Strengthen ISWARA Membership in Malang City - Shanty, Baroya Mila; Satiti, Novita Ratna; Irawati, Sandra (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study addressed the lack of systematic business database and segmentation among Aisyiyah family enterprises in Malang City, which hindered effective economic empowerment planning. It aimed to develop a structured business database and implement clustering methodology to strengthen ISWARA membership through data-driven approaches for more targeted interventions. Method: A participatory action research approach was employed. Data were collected using Google Forms (38 respondents) and printed questionnaires (31 respondents) for members with limited digital access. The data were collaboratively verified with Majelis Ekonomi dan Ketenagakerjaan PDA Malang City, then analyzed using Microsoft Excel to cluster businesses into four main categories and 17 sub-clusters. Practical Applications: The program produced a structured database of 69 businesses, documented 42 products, and enhanced entrepreneurial skills through SWA training (43 participants). The ISWARA Online Market WhatsApp Group was established as a transaction platform, strengthening economic networks and fostering collaboration among members. Conclusion: The research demonstrated that a data-driven, participatory approach can sustainably integrate economic empowerment with digital transformation, providing a replicable model for community-based economic initiatives that strengthens informal leadership and creates measurable impact in women's entrepreneurship development.